THE EFFECT OF EDUCATIONAL INTERVENTION BASED ON TRANSTHEORETICAL MODEL FOR A LOW-SALT DIET AMONG HYPERTENSION PATIENTS: A LITERATURE REVIEW - Hasriani Hasriani; Elly Lilianty Sjattar; Rosyidah Arafat (Universitas Airlangga, 2022)
Introduction: This literature review aimed to describe the educational intervention for a low salt diet based on a trans-theoretical model in hypertensive patients. Methods: This study was a literature review from several databases such as PubMed, Science Direct, Cochrane library, Ebsco, and ProQuest. This study intended to examine studies related to the application of TTM in educating low salt diets in hypertensive patients published in English in the last 5 years. Data were analyzed by summarizing and categorizing studies and interventions. To assess the quality of the articles reviewed, a critical appraisal was assessed using the CASP Randomized Controlled Trial Checklist and the Joanna Briggs Institute Critical Appraisal Checklist for Quasi-Experimental Studies. Result: Five articles were identified and included in the review. A literature review reveals that TTM-based education can change the behavior of hypertensive patients on a low salt diet. Changes in the behavior of a low-salt diet have an impact on clinical changes such as decreased salt excretion in the urine, decreased weight and waist circumference, decreased blood pressure, and the risk of cardiovascular disease. Conclusion: TTM can be used to change the behavior of a low salt diet in hypertensive patients which has an impact on changing biochemical indicators of hypertensive patients.